Mediating And Moderating Effects Of Management Services On The Relationship Of Housing Performance And Stratified Residential Satisfaction - Azian, Fatin Umaira Muhamad (2022)
The performance of medium cost residential buildings is deteriorating due to many complaints reported every year in fulfilling the demand for residential satisfaction. At the same time, the role of management services that can influence housing performance and residential satisfaction relationships also remains unclear and inconclusive. Moreover, most of the studies centered attention on the low-cost housing, and limited studies explored the issue in the context of medium cost high-rise residential buildings. Therefore, this study aims to investigate the housing performance factors influencing residential satisfaction while also considering the role of management services as mediator and moderator. The deductive approach was employed in conjunction with a correlational research design and data gathering via face-to-face survey distribution. This study collected 434 usable responses with an 80.3% response rate by implementing a probability sampling approach. The obtained data were analysed using descriptive statistics (mean score) and the partial least squares structural equation modelling. The study show that respondents were slightly satisfied with the housing scheme. All three (3) housing performance factors significantly affect residential satisfaction with positive effects on housing comfort and function and adverse effects of housing neighbourhood onto residential satisfaction relationship. The findings also indicate that management services partially mediated the housing function-residential satisfaction relationship